Impact of varying levels of soy hulls and β-mannanase enzyme supplementation on growth performance, carcass characteristics, nutrient utilization and blood biochemical profile in broiler chickens - Tauqeer Ahsan; Muhammad Tahir; Rifat Ullah Khan; Shakoor Ahmad; Nazir Ahmad Khan; Yusuf Konca; Ibrahim A. Alhidary; Samia Abdelrahman; Simona Tarricone (Italian Journal of Animal Science)
Two hundred and forty day-old broilers were randomly assigned to six experimental groups in a 2 x 3 factorial design. The birds were fed diets containing soybean hulls (SH) at the levels of 4% and 6% and β-Mannanase (BM) at the concentration of 0%, 0.05% and 0.1%. Results indicated significant effects of SH and BM supplementation on body weight (BW) and weight gain (WG), with birds fed 4% SH and 0.1% BM exhibiting higher (p < 0.05) body weight and weight gain compared to other groups. Feed conversion ratio (FCR) was improved (p < 0.05) in birds receiving 4% SH with 0.1% BM supplementation. However, no significant effects were observed on carcase traits across treatment groups. Regarding nutrient digestibility, birds supplemented with 0.1% BM showed improved (p < 0.05) crude protein (CP) digestibility compared to those without BM supplementation. No significant variations were observed in dry matter, crude fibre and ether extract utilisation among treatment groups. Hematological and serum biochemical parameters were not influenced by SH and BM supplementation, indicating no adverse effects on blood parameters. In conclusion, these findings underscore the potential advantages of incorporating 4% SH and 0.1% BM in broiler diets for enhanced growth performance and nutrient utilisation.